Effects of salinity on three species of gracilaria cultured in tanks - Ferrer, Maria Salvacion R. (College of Fisheries, U. P. in the Visayas, 1998)
Three species of Gracilaria (G. changii, G. firma and G. tenuistipitata) were collected from the coastal areas of Sorsogon and cultured in concrete tanks at SEAFDEC/AQD Tigbauan, Iloilo. Two culture runs were done : (1) May-June, and (2) September-October, 1994. A stocking density of 1 kg m-2 was used with three salinity levels (15, 25 and 35 ppt). Weekly sampling was done to monitor the morphological variations, growth, yield, and pigment levels of test specimens. A 4% alkali pre-treatment for agar extraction was used to determine the agar yield while 1.5% agar sol was used in the analyses of the gel quality. Results showed that salinity strongly affected the morphology, growth, and yield of cultured specimens. Cultured Gralilaria exhibited brittle thalli and lighter color at 15 ppt, while discoloration and mortality of thalli were evident at 25 and 35 ppt during two runs. The three Gracilaria species are euryhaline but they differed in tolerance ranges. The highest growth rates of 3.6% was obtained from G. firma at 35 ppt during the first run, and 3.3% from G. tenuistipitata at 15 ppt during the second run. Significant differences were obtained in G. changii and G. tenuistipitata, and in G. firma and G. tenuistipitata at 25 and 35 ppt during the first run (P< 0.05). The highest estimated production in dry weight were obtained from G. firma with 2.49 kg m-2 y-1 at 25 ppt during first run ; and from G. tenuistipitata with 2.35 kg m-2 y-1 at 15 ppt during second run. Agar yields and gel strengths were higher at higher salinities (25 and 35 ppt), while G tenuistipitata yielded the highest gel strength of 1,082 g cm-2 (35 ppt). This indicates that Gracilariachangii and G. firma are suitable for food agar while G. tenuistipitata has potential for agarose extraction.